The Rivalry of Retired Soldier in the 2019 Indonesian Election - Eko Cahyono; Kamila Suci Cahyani; Muhamad Alvin Fadillah; Yunita Dwi Alfiani (GoResearch - Research & Publishing House, 2022)
The role of retired TNI officers in Indonesian politics is very significant, especially during the New Order era, when they had considerable influence in political and electoral processes. Competition between retired officers can influence election results, as shown by the conflict between the